QDD version 3.1: a user‐friendly computer program for microsatellite selection and primer design revisited: experimental validation of variables determining genotyping success rate. (26th May 2014) - Meglécz, Emese; Pech, Nicolas; Gilles, André; Dubut, Vincent; Hingamp, Pascal; Trilles, Aurélie; Grenier, Rémi; Martin, Jean‐François
Abstract Microsatellite marker development has been greatly simplified by the use of high‐throughput sequencing followed by in silico microsatellite detection and primer design. However, the selection of markers designed by the existing pipelines depends either on arbitrary criteria, or older studies on PCR success. Based on wet laboratory experiments, we have identified the following factors that are most likely to influence genotyping success rate: alignment score between the primers and the amplicon; the distance between primers and microsatellites; the length of the PCR product; target region complexity and the number of reads underlying the sequence. The QDD pipeline has been modified to include these most pertinent factors in the output to help the selection of markers. Furthermore, new features are also included in the present version: (i) not only raw sequencing reads are accepted as input, but also contigs, allowing the analysis of assembled high‐coverage data; (ii) input data can be both in fasta and fastq format to facilitate the use of Illumina and IonTorrent reads; (iii) A comparison to known transposable elements allows their detection; (iv) A contamination check can be carried out by BLASTing potential markers against the nucleotide (nt) database of NCBI; (v) QDD3 is now also available imbedded into a virtual machine making installation easier and operating system independent. It can be used both on command‐line version as well as integrated into a Galaxy server, providing a user‐friendly interface, as well as the possibility to utilize a large variety of NGS tools.